Epidemiological characteristics of stroke incidence from 2017 to 2022 in Songjiang District, Shanghai - SU Xuyan; WANG Yuzhuo; WU Yiling; HE Jingyi; YANG Peng; LANG Dongchen; JIANG Yonggen; ZHAO Genming; ZHENG Yang (Shanghai yufang yixue)
ObjectiveTo investigate the prevalence of stroke in Songjiang District from 2017 to 2022, to analyze the epidemiological characteristics of stroke incidence, so as to provide a scientific basis for the formulation of stroke prevention and control policies.MethodsData of new stroke incidence from 2017 to 2022 in Songjiang District were obtained from the Shanghai Stroke and Acute Myocardial Infarction Registration and Reporting Information System. In addition, different classifications such as time of onset, gender, age group and types of stroke, were statistically analyzed. Statistical indicators, such as the number of incidence, crude incidence rate, standardized incidence rate and average age of incidence were calculated simultaneously. Joinpoint software were used to calculate the annual change percentage (APC) and the trend of stroke incidence in Songjiang District.ResultsFrom 2017 to 2022, the newly reported cases of stroke were 12 988 in Songjiang District, the crude incidence rate was 325.76/105, and the standardized incidence rate was 127.58/105. The crude incidence rate and standardized incidence rate in males were 363.45/105 and 157.17/105, respectively, but 288.68/105 and 99.02/105 in females. The mean age of onset was (73.12±11.75) years, of which the mean age of onset was (70.86±11.96) years for men and (75.91±10.85) years for women. The incidence of stroke increased with age, rising rapidly after 60 years and reaching a peak in the age group of ≥ 80 years old. The crude incidence rate and standardized incidence rate of stroke in Songjiang District showed a downward trend from 2017 to 2022, with an APC of -6.20% and -8.01%, respectively (P=0.018, 0.007). The newly reported stroke was dominated by ischemic stroke, accounting for 82.81% of the total cases, with a crude incidence rate of 269.77/105 and a standardized rate of 103.84/105. The incidence of stroke presented seasonal characteristics, with the highest incidence in winter, accounting for 26.11% of the whole year.ConclusionThe incidence rate of stroke in Songjiang District shows a declined trend, but the overall incidence is still at a high level. The situation of prevention and control is still serious, with a heavy disease burden. It is necessary to strengthen health education and disease management for the elderly.